Praktik Penyelesaian Sengketa Keluarga di Kabupaten Kepulauan Seribu ((Studi Peran Tokoh Agama, Masyarakat, dan Aparat Negara) - Kamarusdiana; Rasyid, Harun; Ali Imron; Purkon, Arip; Rosyid, Maskur; Suma, M. Amin (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Divorce outside religious courts often occurs in the Kepulauan Seribu community. As a result, the rights of wives and children after divorce are neglected. This article aims to examine in more depth the factors and resolution of divorce disputes outside of Court. This article is qualitative, with data sources obtained through interviews and document study. This article finds that four factors cause divorce outside religious courts: the location of the Kepulauan Seribu is very far from the site of the North Jakarta Religious Court, the economy, weather conditions and the educational level of the people of the Kepulauan Seribu. The resolution of family disputes is carried out using three processes: deliberations, mediation, and Mobile Sessions conducted by the North Jakarta Religious Court.